Validitas dan Praktikalitas Lembar Kerja Peserta Didik (LKPD) Materi Kingdom Plantae Berbasis Pendekatan Saintifik untuk Peserta Didik Kelas X SMA/MA - Lestari, Lasmi; Alberida, Heffi; Rahmi, Yosi Laila (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This is a development research to produce valid and practice Student Worksheet. This research used 3 steps from 4-D models those are defined, design and development. The subject of this research was 28 students class X from SMA Negeri 1 Padang, validated by 2 lecturers and 2 teachers. The object of this research was based student worksheet that validated by 4 validators. The data in this research are primary data consisting of validity and practicality. The result of validity was 87,30% with criteria valid, practicality by teachers was very practiced with value 85,94% and by the student was practicing with value 83,05%.